Estrés en docentes de la facultad de enfermería de la Universidad Antonio Nariño en tiempos de pandemia Covid-19 (2021)
Throughout history, stress has been one of the triggers for the development of chronic diseases on many occasions, influencing the profession that is practiced, in this case, university teaching, it is one of the professions that are ascribes the development of high levels of stress taking into account all the context that this means